Ekspresi cyclooxygenase-2 (COX-2) pada penderita rinosinusitis kronis - Agus Multazar; Siti Nursiah; Andrina Rambe; Ida Sjailandrawati Harahap (PERHATI-KL, 2012)
Background: Chronic rhinosinusitis (CRS) is an inflammation of the nasal and paranasal sinus mucosa, which are closely related to the involvement of ostiomeatal complex as the drainage pathway of of maxillary and frontal sinuses. Inflammation or edema at the ostiomeatal complex could cause drainage problems leading to rhinosinusitis. Increased expression of COX-2 regulation was considered to play an important role in the development of CRS and increased airway inflammation in the nasal mucosa and paranasal sinuses. Purpose: To find out the expression of Cyclooxygenase-2 in our CRS patients. Methods: This descriptive research was conducted on July 2011 - December 2011 at ENT Department and Pathology Anatomy Department of Medical Faculty of Sumatera Utara University/H. Adam Malik General Hospital, Medan, to all patients diagnosed with CRS and underwent sinus surgery on July 2011 - December 2011. Results: The highest proportion of pain in patients with CRS is facial pain/pressure and headache with nasal congestion which was 78.6%. Multisinusitis on paranasal sinus CT scan was 88.0%. There was a significant correlation between the proportion of pain with the expression of COX-2 (p = 0.033). There was a significant correlation in proportion between the number of sinuses involved with the expression of COX-2 (p = 0.002). Conclusion: This study found positive expression of COX-2 was 84,0%, while negative expression was 16,0% in our rhinosinusitis patients. This lead to conclusion that upregulation of COX-2 expression is thought to play a role as a mediator in the development of CRS. Keywords: chronic rhinosinusitis, ostiomeatal complex, cyclooxygenase-2, immunohistochemical. Abstrak : Latar belakang: Rinosinusitis kronis merupakan peradangan mukosa hidung dan sinus paranasal yang erat hubungannya dengan keterlibatan kompleks ostiomeatal atau celah sempit di etmoid anterior, yang merupakan serambi muka bagi sinus maksila dan frontal. Bila terdapat gangguan di daerah kompleks ostiomeatal seperti inflamasi atau edema maka hal itu akan menyebabkan gangguan drainase sehingga terjadi rinosinusitis. Peningkatan regulasi ekspresi COX-2 diperkirakan memegang peran penting sebagai mediator dalam terjadinya rinosinusitis kronis dan peningkatan inflamasi saluran napas di mukosa hidung dan sinus paranasal. Tujuan: Mengetahui ekspresi cyclooxygenase-2 pada penderita rinosinusitis kronis di RSUP H. Adam Malik, Medan. Metode: Penelitian ini bersifat deskriptif dilakukan di Departemen THT-KL FK USU/RSUP H. Adam Malik, Medan dan Departemen Patologi Anatomi FK USU. Penelitian dilakukan bulan Juli - Desember 2011 pada seluruh penderita yang didiagnosis rinosinusitis kronis, yang menjalani operasi sinus di Divisi Rinologi Departemen THT-KL FK USU/RSUP H. Adam Malik, Medan bulan Juli 2011 - Desember 2011. Hasil: Proporsi rasa nyeri terbanyak pada penderita rinosinusitis kronis adalah rasa nyeri/ nyeri tekan wajah, sakit kepala disertai dengan hidung tersumbat 78,6%. Multi sinusitis pada pemeriksaan CT-Scan sinus paranasal sebanyak 88,0%. Ada hubungan yang bermakna antara jumlah sinus yang terlibat dengan ekspresi COX-2 (p = 0,002). Ada hubungan yang bermakna antara proporsi rasa nyeri dengan ekspresi COX-2 (p=0,033). Kesimpulan: Pada penelitian ini didapati pada penderita rinosinusitis kronis, ekspresi COX-2 yang positif yaitu sebanyak 84,0%, sedangkan yang negatif sebanyak 16,0%. Diperkirakan peningkatan regulasi ekspresi COX-2 berperan sebagai mediator dalam terjadinya rinosinusitis kronis. Kata Kunci: rinosinusitis kronis, kompleks ostiomeatal, cyclooxygenase-2, imunohistokimia.